2002
DOI: 10.1002/1438-9312(200201)104:1<19::aid-ejlt19>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of lipid oxidation in the presence of cinnamic acid derivatives

Abstract: The effects of seven (prenyl-and methoxy-) derivatives of cinnamic acid (0.1 mM) on the kinetics of lipid (sunflower oil triacylglycerols, TGSO) bulk phase oxidation at 80°C have been compared. Synthesis of prenyl cinnamic acid derivatives: 3-prenyl-4-hydroxy-cinnamic acid (PHC), 3,5-diprenyl-4-hydroxy-cinnamic acid (DPHC), 2,2-dimethyl-6-carboxy-ethenyl-2H-benzopyran (DMCB), 2,2-dimethyl-6-carboxy-ethenyl-8-prenyl-2H-benzopyran (DCEPB) present in Brazilian propolis has been performed. The monoprenyl derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Lipid hydroperoxides (LOOH) may break down into free radicals, which are responsible for subsequent autoxidation reactions. In this regard, phenolic compounds and their derivatives are very efficient substances in avoiding autooxidation processes [128]. For instance, CGA was found to protect human erythrocytes from oxidative stress produced by low levels of lipid hydroperoxides in artificial liposomes [142].…”
Section: Amidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipid hydroperoxides (LOOH) may break down into free radicals, which are responsible for subsequent autoxidation reactions. In this regard, phenolic compounds and their derivatives are very efficient substances in avoiding autooxidation processes [128]. For instance, CGA was found to protect human erythrocytes from oxidative stress produced by low levels of lipid hydroperoxides in artificial liposomes [142].…”
Section: Amidationmentioning
confidence: 99%
“…For instance, CGA was found to protect human erythrocytes from oxidative stress produced by low levels of lipid hydroperoxides in artificial liposomes [142]. Kortenska et al [128] investigated the kinetics of lipid peroxidation in the presence of cinnamic acid derivatives. For this purpose, the triacylglycerols of sunflower oil were used as lipid samples in lipid oxidation model.…”
Section: Amidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies establish a relationship between the antioxidant activity of ethanolic extracts of propolis and their contents of phenolic compounds, such as the flavonoids. 5,22,23 The analysis of variance revealed that the propolis concentration, the ethanol content, and their interaction are significant (P < 0.0500) for the content of total phenolic compounds: y = + 70.3855 + 2.4794 x 1 + 9.9669 x 2 -10.1251 x 1 x 2 , where y = content of total phenolic compounds, x 1 = ethanol content, x 2 = propolis concentration and x 1 x 2 = interaction between the propolis concentration and the ethanol content. The effect of the ethanol content was only 3%, while those of the propolis concentration and the "extract concentration × ethanol content" interaction were more important for the content of total phenolic compounds, with contributions of 46 and 48%, respectively (Figure 1c).…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
“…Studies report that mono-and diprenyl ortho-substituted phenolic acids (PHC and DPHC) show higher antioxidant activity in comparison with unsubstituted p-coumaric acid. 22 Such compounds are possibly detected as the ions of m/z 231, 299 and 163, respectively (Figure 3). In addition, other studies of the effects of various parameters on the propolis extraction yield 23 also observed increased yield for compounds derived from p-coumaric acid with increased ethanol content, such as mono-and diprenyl ortho-substituted phenol acids.…”
mentioning
confidence: 99%